Moroccan actinobacteria with promising activity against toxic cyanobacteria Microcystis aeruginosa - Zerrifi, S.E.A. (2020)
In recent decades, harmful cyanobacterial blooms (HCBs) have become a severe hazard for human health mainly in drinking water resources and are responsible for serious ecological disturbances in freshwater ecosystems. The present study aims to explore the potential of actinobacteria isolated from sediment samples collected from Moroccan salt river to control HCBs mainly through Microcystis aeruginosa lysis. In order to investigate the possible anti-cyanobacterial response mechanisms, the antioxidant enzyme activities of M. aeruginosa cells were analysed. Anti-cyanobacterial activity was tested using the agar cylinder method against the toxic cyanobacteria Microcystis aeruginosa. Amongst the twenty-three isolates tested, only one showed promising anti-cyanobacterial activities with inhibition zone (ZI) equal to 22.00 mm, minimum inhibitory concentration (MIC) equal to 19.53 mg/L and minimum bactericidal concentration MBC equal to 39.06 mg/L. Phylogenetic analysis of the near-complete 16S rRNA gene sequence indicated that the strain DS1R1 belongs to the genus Streptomyces and has the highest similarity (100%) to Streptomyces sp. Indeed, M. aeruginosa growth, chlorophyll-a and protein content were significantly reduced by Streptomyces sp. DS1R1 extract. Superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA) were significantly elevated after treatment with Streptomyces sp. DS1R1 extract. These experimental findings provided insights in the development of a new eco-friendly procedure based on the use of actinobacteria for toxic cyanobacterial bloom bio-control.